Nanovectorization of metformin with phytochemicals for cancer therapy: A scoping review - Abraham, Wall-Medrano (2024)
This work aimed to review the scientific evidence on the anticancer potential of metformin with phytochemicals, nano-vectorized in surface-decorated nanocarriers. Given that cancer is a disease with a significant impact on both global mortality rates and health expenditure and that conventional therapies (surgery, radiotherapy and chemotherapy) have proven deleterious side effects, the search for new molecules with anticancer properties has climbed. Metformin is an antidiabetic drug with proven chemotherapeutic and biosafety properties, currently considered as an oncological repositioning drug. Certain phytochemicals also have proven anticancer properties and are highly biocompatible. The synergy of both metformin + phytochemicals has recently emerged as a promising mix with elucidated mechanisms and molecular targets for certain types of cancer. The challenge of improving their pharmacokinetic properties and bioavailability has driven research in nanotechnology to improve their biodistribution, cellular internalization and anticancer efficacy. Current knowledge is mostly based on preclinical evidence [in vitro (cell lines)/in vivo (rodents)] but confirmation in controlled clinical trials is necessary to boost their commercial use shortly